Tabanidae (Diptera) da Amazônia. II. Descrição de nove machos de Mutucas - (:unkn) unknown (Museu Paraense Emilio Goeldi, 1982)
There is a marked variation in the degree of dimorphism between the sexes of the tabanids. New data are presented on the methods of collecting these insects. Males of nine species of mutucas are described: Chrysops formosus, Diachlorus fuscistigma. D. podagricus, D. scutellatus, Fidena pseudoaurimaculata, Philipotabanus stigmaticalis, Stenotabanus (Phorcotabanus) cinereus, S. (Cretotabanus) cretatus and Stypommisa captiroptera. Several illustrations are presented highlighting the main dimorphisms and characters of the genitalia. By observations and results of the collected collections, it is proposed the relation of the males of tabanídeos with the flowering of the trees in the forest and that these fly in tree strata higher than the females. Justify the need for broader and more urgent studies of these insects in the region, considering the rapid transformation of their habitats by the use of spaces.
Keywords: Tabanídeos; Mutucas; Machos; Chrysops formosus; Diachlorus fuscistigma; D. podagricus; D. scutellatus; Fidena pseudoaurimaculata; Philipotabanus stigmaticalis; Stenotabanus (Phorcotabanus) cinereus; S. (Cretotabanus); Stypommisa captiroptera; Genitália; CNPQ::CIENCIAS BIOLOGICAS::ZOOLOGIA